Upworkers in Finland: Survey Results - Mika Pajarinen; Petri Rouvinen; Jörg Claussen; Jari Hakanen; Anne Kovalainen; Tobias Kretschmer; Seppo Poutanen; Mareike Seifried; Laura Seppänen (The Research Institute of the Finnish Economy (ETLA), 2018)
Upwork is the world's largest online labor market platform connecting clients with freelance professionals from various disciplines ranging from administrative support to web development. This study documents the main findings of the Upworkers in Finland survey conducted in December 2017. The survey targeted all freelancers listed on the platform who (a) claimed to reside in Finland and (b) had earned at least 1 since signing up. Of the 207 such freelancers found publicly listed on Upwork on 8 December 2017, 58.9% responded to our online questionnaire. Most Upworkers in Finland are translators, followed by designers and coders. They are typically less than 30 years old, involved in higher education or training (or already have at least a college-level degree), and live in the capital region or another urban area. Approximately one-third are immigrants or other nonnative speakers. They have a strong preference for entrepreneurship/self-employment over paid/salaried employment. Independence, flexibility, and extra earnings are particularly motivators for online work engagement. The respondents are both quite fond of the platform and satisfied with their current online work arrangement.
Keywords: D26; J22; M55; O33; 330; Platform economy; Future of work; Online labor markets; Upwork; Finland; Freie Mitarbeiter; Internetportal; Finnland